Accountants in the information age : the internet approach. - Lee, Boon Ann. (2013)
With an estimated 2000 people joining each day, the Internet is the fastest growing network in the world. The impact and usefulness of the Internet parallels the history of personal computing, with a lag of about ten years. About ten years ago, personal computers brought computing from the realm of technical gurus to the general public: “the rest of us,” as Apple said in their advertisements. The Internet is currently making the same transition. It is becoming an essential tool for everyone, even the business community realize its impact on its practices.